Memahami Kompleksitas Kepribadian Manusia: Review Deskriptif Buku 'Psikologi Kepribadian' Karya Alwisol - Sari Nalurita; Yusi Riska Yustiana (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This descriptive review aims to critically examine the book "Psikologi Kepribadian" by Alwisol, a fundamental literature in the study of personality psychology in Indonesia. This analysis dissects the book's theoretical scope, which encompasses various approaches to personality psychology, ranging from classical psychoanalysis, neo-Freudian, humanistic, behavioral, cognitive, to trait approaches. The book's primary strengths lie in its ability to present a balance between various theoretical perspectives, systematic and structured presentation, and accessibility for Indonesian readers through the use of clear Indonesian language. However, key limitations are also identified, namely the limited depth of discussion for each theory given the breadth of material coverage, and the lack of case examples from the Indonesian context. In conclusion, this book is an essential resource for students and practitioners of psychology in Indonesia, providing a solid theoretical foundation for understanding the complexity of human personality from various theoretical perspectives. Keywords: personality psychology, book review, Alwisol, personality theory, psychoanalysis, humanistic, behavioral, trait   Abstrak Review deskriptif ini bertujuan untuk mengkaji secara kritis buku "Psikologi Kepribadian" karya Alwisol, sebuah literatur fundamental dalam studi psikologi kepribadian di Indonesia. Analisis ini membedah cakupan teoretis buku yang mencakup berbagai aliran psikologi kepribadian, mulai dari pendekatan psikoanalisis klasik, neo-Freudian, humanistik, behavioral, kognitif, hingga pendekatan trait. Kekuatan utama buku ini terletak pada kemampuannya menyajikan keseimbangan antara berbagai perspektif teoretis, penyajian yang sistematis dan terstruktur, serta aksesibilitas bagi pembaca Indonesia melalui penggunaan bahasa Indonesia yang lugas. Meskipun demikian, diidentifikasi pula keterbatasan utama, yakni kedalaman pembahasan yang terbatas untuk setiap teori mengingat luasnya cakupan materi, serta kurangnya contoh kasus dari konteks Indonesia. Kesimpulannya, buku ini merupakan sumber daya esensial bagi mahasiswa dan praktisi psikologi di Indonesia, menyediakan landasan teoretis yang kokoh untuk memahami kompleksitas kepribadian manusia dari berbagai sudut pandang teoretis.. Kata kunci: psikologi kepribadian, review buku, Alwisol, teori kepribadian, psikoanalisis, humanistik, behavioral, trait